Pengaruh Pelaporan dan Pelayanan SPT Tahunan dengan Menggunakan e-filling Terhadap Tingkat Kepuasan Wajib Pajak di KPP Pratama Wonocolo Surabaya - Lidya Putri Nanda Sembiring; Taufik Kurniawan (CV ODIS, 2022)
This assessment is to be able to understand and investigate the reporting and service of annual tax returns using an electronic filling of the level of taxpayer satisfaction. All of these reviewers are taxpayers at KPP Wonocolo Surabaya. An example used is a simple random sampling method where 25 speakers were taken. This method of analysis uses the Classical Assumption Test method. The results of this review inform that KPP Wonocolo Surabaya to the taxpayer community has a concrete impact on the level of satisfaction and services have a concrete impact on the level of satisfaction of taxpayers